Determining the Coordinates of Control Points in Hydrographic Surveying by the Precise Point Positioning Method - Akpinar, Burak; Aykut, Nedim Onur (CAMBRIDGE UNIV PRESS, 2017)
After Global Navigation Satellite Systems (GNSS) were first used in the field of hydrography in 1980, developments in hydrographic surveying accelerated. Survey precision in hydrography has been improved for both horizontal and vertical positioning and seafloor acoustic measurement by means of these new developments. Differential Global Positioning System (DGPS), Real Time Kinematic (RTK) and Network RTK (NRTK) techniques are the satellite-based positioning techniques that are commonly used in shallow water surveys and shoreline measurements. In line with these developments, the newer Precise Point Positioning (PPP) has been introduced. Combining precise satellite positions and clocks with dual-frequency GNSS data, PPP can provide position solutions from the centimetre to decimetre level. In this study, the coordinates of control points were determined by using the Post-Process PPP (PP-PPP) technique. Seven test points, which are the points of the Continuously Operating Reference Station - Turkey (CORS-TR) network, are selected near the shorelines within Turkey. The 24-hour data was split from one to six hours by one hour periods. Automatic Point Positioning Service (APPS) was selected to process the data. The poisoning error of the test points were given and compared with International Hydrographic Organization (IHO) S44 hydrographic survey standards.
Keywords: Precise point positioning; Hydrographic surveying; Control point coordinates; GNSS; GPS; NETWORK; GLONASS; SYSTEM; Engineering; Oceanography